* Virulence factors, antimicrobial resistance genes and protein structure of crohn's disease-derived. (13th March 2011) - Elliott, T; Hudspith, B; Rayment, N; Randall, L; Wu, G; Boussioutas, A; Hermon-Taylor, J; Brostoff, J; Petrovska, L; Sanderson, J D
Abstract : Introduction: Intracellular Escherichia coli isolates are found in up to 60% of gut biopsies from patients with Crohn's disease (CD). Although adherent invasive E coli (AIEC) are described, other intracellular E coli are frequently isolated but specific pathogenic determinants for these have not been identified by conventional techniques. DNA microarray and Matrix-assisted laser desorption/ionisation time of flight (MALDI-TOF) mass spectrometry enable rapid and accurate DNA and proteomic analysis of bacteria. Aims: To investigate for virulence and antimicrobial resistance (AMR) genes in, and analyse the structure of CD-related intracellular E coli isolates. Methods: 17 E coli strains were isolated using gentamicin protection assay from gut biopsies of 17 CD patients (ileal n=7, colonic n=10). DNA was extracted for analysis by DNA microarray (Prodigy) of 392 virulence and AMR genes. DNA PCR was performed for an additional 18 virulence genes. For Bruker Biotyper MALDI-TOF sample preparation, several colonies of each bacterial strain were spotted onto target plate and prepared as described previously. 10 replicates of the mass/charge spectra for each strain were compared to spectra from a bacterial database. Results: Virulence factors were identified by DNA microarray in a number of E coli strains including senB (encodes enterotoxin), Iha (encodes an adhesin) Sat (toxin of uropathogenic E coli ), iron regulation genes and microcin synthesis genes. DNA PCR revealed additional virulence factors including ibeA (associated with E coli invasion in neonatal meningitis) in 2 strains. A minority of strains were positive for AMR genes relating to β-lactams, sulphonamides, tetracycline and streptomycin. MALDI-TOF analysis confirmed the bacteria as E coli and clustered the Crohn's disease E coli strains together and separate from other E coli strains on the Bruker database. There was no clustering within CD strains in relation to disease or biopsy site or immunomodulation. Conclusion: Although CD appears to be at least in part a host immune disorder, pathogenic factors of various organisms may still play a role in pathogenesis. A number of genes encoding for virulence factors have been identified in a proportion of CD-related E coli strains which warrant further investigation (eg, whole gene sequencing and functional assays). Most strains had no antimicrobial resistance genes. Further MALDI-TOF comparison of CD-related bacterial structure with commensal and IBD-related bacteria may be revealing.